2019
DOI: 10.4028/www.scientific.net/kem.823.33
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Texture on Abrasive Wear

Abstract: Friction happens everywhere. Abrasives generated in tribological process will result in secondary wear. Abrasive wear is a kind of rather common but harmful wear, which is the main reason for the damage of fifty-percent mechanical components by friction. Surface texturing is an effective method to improve the tribological and lubricating performance of tribo-pairs. In this paper, with different-size diamond particles added into the lubricant and a surface of the tribo-pairs textured by different parameters (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Feng et al [21] indicated that the cutting force and cutting temperature could be significantly reduced when a textured tool was used. As a conclusion, the textures on the tool surface can effectively reduce the tool-chip contact surface, reduce cutting temperature and cutting force, store lubricant, improve the contact state, and decrease the adhesion phenomenon [22][23][24][25]. However, the effect of sinusoidal textures and rhombic micro textures of tools on the cutting performance of titanium alloy is still unclear, which is necessary to be studied to further improve the cutting efficiency and surface quality of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [21] indicated that the cutting force and cutting temperature could be significantly reduced when a textured tool was used. As a conclusion, the textures on the tool surface can effectively reduce the tool-chip contact surface, reduce cutting temperature and cutting force, store lubricant, improve the contact state, and decrease the adhesion phenomenon [22][23][24][25]. However, the effect of sinusoidal textures and rhombic micro textures of tools on the cutting performance of titanium alloy is still unclear, which is necessary to be studied to further improve the cutting efficiency and surface quality of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%